ШАҢАРАҚТА БАЛАНЫҢ ЖАС ӨЗГЕШЕЛИКЛЕРИНЕ ЫЛАЙЫҚ ТӘРБИЯ БЕРИЎ МАШҚАЛАЛАРЫ - Пазылов, М.А. (FAN va JAMIYAT, 2020)
In this article it is said about the problems of the children's upbringing in the family, taking into consideration the children's age and according to it the selection of suitable ways in the upbringing.